Legal and practical aspects of access to health care for persons with hearing loss in selected European countries - Kulińska, Karolina (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article presents the outcomes of legal research combined with quantitative and qualitative research review concerning access to health care for people with hearing loss in selected European countries: United Kingdom, Federal Republic of Germany and Republic of Poland. The main objective was to verify if and how this issue, especially communication and access to information, is solved in different legal systems. Secondly, by comparing the established legal framework in each country with available data on actual quality of healthcare provision, it was assessed whether any regularities between the chosen models of regulating rights of people with hearing loss and real-life adjustments for those patients can be detected. The objective scope of the research includes any type of hearing loss which affects spoken language communication, that is not only d/Deaf but also deafblind and hard of hearing persons, if only their primary and/or preferred way of communication is the not-spoken one. The main findings of the performed analysis are that key sources of barriers in access to healthcare are the lack of awareness on the side of both patients (regarding their rights) and healthcare providers (specificity of hearing impairments) and the fact that enhancements in the professional status of sign language interpreters and other communication assistants are needed
Keywords: słuch; ubytek słuchu; język migowy; opieka zdrowotna; tłumacz języka migowego; tłumaczenia medyczne